The Toronto Concussion Study: Sense of smell is not associated with concussion severity or recovery. (12th May 2022) - Foster, Evan; Bayley, Mark; Langer, Laura; Saverino, Cristina; Chandra, Tharshini; Barnard, Claire; Comper, Paul
ABSTRACT: Objective: To examine sense of smell as a biomarker for both severity and duration of post-concussion symptoms. Methods: Participants were recruited prospectively from an outpatient concussion clinic. Sense of smell was assessed using the University of Pennsylvania Smell Identification Test (UPSIT) within 7 days, and 4, 8 – or 16-weeks post-injury. UPSIT normative data were used as normal controls. The main outcomes were: symptom severity on the Sport Concussion Assessment Tool 3 (SCAT3) symptom inventory and time to physician-declared recovery. Results: A total of 167 participants (mean age 32.9 [SD, 12.2] years, 59% female [n = 99]) were classified at 1 week post injury as follows: severe hyposmia in 5 (3%), moderate hyposmia in 10 (6%), mild hyposmia in 48 (29%), and normosmia in 104 (62%) individuals. A convenience sample of 81 individuals with concussion were tested at follow-up. Acute impairment of sense of smell following concussion was not associated with symptom severity on the SCAT3 or time to recovery. Sense of smell was stable from baseline to follow-up in this population. Conclusion: This study provides evidence that routine testing of sense of smell in individuals with concussion is not warranted as a biomarker for severity of concussion and concussion recovery.